FLEKSIBILITAS KOGNITIF DALAM BAHTS AL-MAS?IL NAHDLATUL ULAMA - Muhammad Adib; Muhammad Hasbulloh Huda (LP3M IAI Al-Qolam, 2020)
This study is a review of Islamic law regarding cognitive flexibility in the fatwas of Nahdlatul Ulama (NU)’s Bahtsul Masail. Using epistemological approaches, this study suggests that cognitive flexibility in Bahtsul Masail NU is strongly rooted in Aswaja as NU's religious reasoning. Cognitive flexibility in the Bahtsul Masail NU is reflected in the practice of selecting literatures and opinions of mazhab scholars and the practice of interpreting the yellow book (kitab kuning) texts.